The Big Prostate (Springer International Publishing, 2018)
This book will explore and explain the best diagnostic and treatment strategies for men with a big prostate. Men are living longer and the opportunity to develop significant benign prostatic hyperplasia is increasing. Men with very large prostates can often be extremely challenging to manage and all urologists and healthcare professionals carrying out general urology and managing men with prostate problems will have come across this issue. There are a number of diagnostic, interventional, and surgical management options available, with some of these being more suited to a large prostate than others. The various treatment strategies and their evidence base are discussed. Valuable tips from expert authors who are experienced in the management of the particularly large prostate are included to allow readers to be confident when managing this increasingly important and prevalent group of patients. This book is of particular use to healthcare practitioners who manage men with BPH in the outpatient or emergency setting, as well as those in the operating theatre who want further tips on how to deal with the particularly big prostate. .